Życie i twórczość Józefa Łukaszewicza w świetle artykułów wspomnieniowych prasy XIX-wiecznej - Góra, Barbara (Studia Edukacyjne, 2023)
The article focuses on Józef Łukaszewicz (1799-1873), a historian, director of the Raczyński Library, librarian, publisher, editor, and founder of Tygodnik Literacki, Przyjaciel Ludu and Orędownik Naukowy. Author of monographs on the history of cities in terms of material culture, history of Catholicism and the Reformation in Poland in the 17th century, as well as on the history of education. The review of 19th-century press included in the article is a selection from the published texts after Łukaszewicz’s death, summarizing the life and legacy of this distinguished scholar, an outstanding figure who made a lasting mark on the history of the Raczyński Library, the history of the city of Poznań and the region of Wielkopolska.